Enhancing efficiency and quality control: Implementing TQM in Pakistani construction - Waheed , Muhammad; Abbas, Mutahir (Journal of Commerce, Management, and Tourism Studies, 2024)
Recent advancements in construction technology and production have increasingly integrated Total Quality Management (TQM) systems to enhance process oversight and prevent errors proactively. TQM focuses on continuous improvement throughout an organization, emphasizing systemic changes rather than merely assessing performance. This research aims to explore the significance of TQM in the construction industry, an area lacking comprehensive study. The primary objectives are to evaluate the impact of TQM on quality control, customer satisfaction, and risk mitigation within the sector. The study employs a mixed-method approach, combining quantitative surveys with qualitative interviews to gather data from construction professionals and stakeholders. The analysis involves assessing the correlation between TQM practices and improvements in project outcomes, such as reduced defects, increased client satisfaction, and enhanced risk management. Findings suggest that implementing TQM leads to substantial improvements in quality control and customer satisfaction while effectively mitigating risks. The conclusion highlights the critical role of TQM in fostering a culture of continuous improvement in construction, recommending further research to refine TQM practices and evaluate their long-term effects on industry performance.